1991
DOI: 10.1021/bi00243a001
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus reverse transcriptase ribonuclease H: specificity of tRNALys3-primer excision

Abstract: Two model substrates were prepared to examine the mechanism of tRNA-primer excision catalyzed by reverse transcriptase associated ribonuclease H (RT-RNase H). The first model substrate contained sequences from the HIV genome and was designed to be structurally similar to the DNA-extended tRNA created by initiation of minus-strand DNA synthesis during retroviral replication. The DNA-extended RNA was a template and was annealed to a DNA oligonucleotide that primed reverse transcription of the RNA in the template… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
79
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 23 publications
5
79
0
Order By: Relevance
“…The RNase H cleavages that remove the tRNA primer, and the cleavages that generate and remove the polypurine tract (ppt) primer define the ends of the unintegrated linear viral DNA that is the substrate for the integration reaction. HIV-1 RT removes the tRNA one base from the RNA-DNA junction (15)(16)(17)(18); other retroviral RTs remove the entire tRNA (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The RNase H cleavages that remove the tRNA primer, and the cleavages that generate and remove the polypurine tract (ppt) primer define the ends of the unintegrated linear viral DNA that is the substrate for the integration reaction. HIV-1 RT removes the tRNA one base from the RNA-DNA junction (15)(16)(17)(18); other retroviral RTs remove the entire tRNA (2).…”
mentioning
confidence: 99%
“…The ribonucleotide (rA) at the 5Ј end of the minus strand is derived from the tRNA. HIV-1 RT removes the tRNA one base from the RNA-DNA junction (15)(16)(17)(18); other retroviral RTs remove the entire tRNA (2). (vii) The structure of full-length viral DNA.…”
mentioning
confidence: 99%
“…In addition, (ϩ), or second-strand DNA synthesis requires highly specific RNase H cleavage to release the 3Ј OH of the polypurine tract (PPT) primer (3)(4)(5). Finally, the (ϩ) and (Ϫ) strand RNA primers (the PPT and a host-derived tRNA, respectively) must be precisely removed from nascent DNA to preserve the integrity of the 5Ј and 3Ј long terminal repeat termini of the provirus for recognition by the retroviral integration machinery (3,6,7). Each of these events can be considered candidates for therapeutic intervention by antiviral agents in the ongoing effort to stem the progression of human immunodeficiency virus (HIV) infection and acquired immunodeficiency syndrome.…”
mentioning
confidence: 99%
“…Several groups have studied the coordination of DNA polymerase and RNase H activities (Oyama ef a/., 1989;Luo and Taylor, 1990;Wöhrl and Moelling, 1990;Furfine and Reardon, 1991 a;Furfine and Reardon, 1991b; Gopalakrishnan ef a/., 1992; Kati ef a/., 1992). The two activity site are separated by 10 to 19 nucleotides (Gopalakrishnan ef a/., 1992; Kati ef a/., 1992).…”
Section: Rnase Hmentioning
confidence: 99%
“…Although there is considerable support for coupling of DNA polymerase and RNAse H activities, there are both biochemical (Huber ef a/., 1989; DeStefano ef a/., 1991b) and genetical data(Telesnitsky and Goff, 1993c) that suggested uncoupled activities. One way to rationalize these results is to imagine that RNase H can function in two modes, one dependent upon and the other independent of polymerization (Furfine and Reardon, 1991b;Gopalakrishnan ef a/., 1992). Genetic studies indicated that the uncoupled mode may be sufficient for low level viral replication (Telesnitsky and Goff, 1993c).…”
Section: Rnase Hmentioning
confidence: 99%